Adolescent girls' connectivity in an occupational efficacy workshop: Understanding avoidance. (July 2016) - Oppenheim-Shachar, Sigal; Benjamin, Orly
Synopsis: Skeggs' notion of 'emotional politics' cites a dynamic in girls' worlds that is applicable to Joseph's theory of connectivity vis-à-vis girls' participation in after-school activities. Here, we deploy this theoretical connection to examine under what conditions avoidance characterizes Israeli at-risk urban girls' responses to a workshop targeting and promoting their occupational efficacy. Analyzing 11 'avoiding' girls out of 34 participants, we found that when participants experienced the workshop content as contradicting their family experiences, they used positive feelings of family belonging, or connectivity, as a resource in facing the workshop's demands. To reduce the sense of conflict between familial expectations and the occupational efficacy workshop, and hence minimize avoidance, we concluded that future projects of this type should offer material resources and mentors that would help girls negotiate the workshop's content at home. Highlights: It is important to understand avoidance among adolescent girls. Being the 'good girl' at home is prioritized over promises for 'occupational efficacy'. Girls may remain suspicious of occupational efficacy workshop if it triggers negative feelings about the self. Avoiding girls have intensified needs: for material resources; for individual mentoring; and for mediating negotiation with parents.